Reinterpretasi Teori Lombroso dalam Konteks Hukum Pidana Modern: Kapan Born Criminal Menjadi Insanity Defense? - Zul Khaidir Kadir (Jurnal Litigasi Amsir, 2024)
The born criminal theory, rooted in biological determinism, explains that criminality is the result of genetically inherited traits that can be recognized through distinctive physical characteristics, indicating an evolutionary regression to a primitive stage of humankind. On the other hand, the insanity defense is a criminal law doctrine that states that individuals who suffer from mental disorders at the time of committing a crime cannot be held accountable because it eliminates the evil mental attitude. Although Lombroso's theory emphasized that criminals are innately predisposed to crime due to uncontrollable biological factors, this concept has rarely been explored within the insanity defense framework. This study used qualitative research methods. Qualitative research is research to understand social phenomena and human behavior by processing descriptive data. This research was conducted using a conceptual approach. The data collection method was collected using library research, then analyzed using qualitative methods and presented descriptively. Research findings show that meeting point between Lombroso's born criminal theory and the concept of insanity defense in modern criminal law lies in the recognition that biological factors can influence a person's criminal behavior, albeit with a more scientific and comprehensive understanding today. However, unlike Lombroso's view that ignores free will, modern law views that these biological influences do not completely determine a person's behavior, but must be evaluated individually in the context of the defendant's mental capacity at the time of the crime.